2022
DOI: 10.1186/s13567-022-01026-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain glucomannan supplementation modulates immune responsiveness, as well as intestinal microbiota, and impacts infection of broiler chickens with Salmonella enterica serotype Enteritidis

Abstract: The zoonotic pathogen Salmonella enterica serotype Enteritidis (SE) causes severe disease in young chickens. Restriction on antibiotic use requires alternative SE control strategies such as nutritional solutions to improve the resistance of chickens. In this study, chickens were fed long-chain glucomannan (GM) or standard diet and challenged with SE at seven days of age. During 21 days post-infection (dpi), we determined numbers and responsiveness of natural killer (NK) and T cells in ileum and spleen, and SE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…However, it appears that certain fractions of cereal grains can be a source of several β-glucans, which are also potentially fermentable, resulting in the antagonism of pathogens such as Salmonella [ 103 ]. Furthermore, recent studies have observed that other dietary fibers, such as long-chain glucomannan, can reduce the colonization of Salmonella in the intestines of birds, thereby reducing the excretion of the bacteria into the environment, while also stimulating the immune response of the animal [ 104 ].…”
Section: Innovative Control Tools In Development Against S ...mentioning
confidence: 99%
“…However, it appears that certain fractions of cereal grains can be a source of several β-glucans, which are also potentially fermentable, resulting in the antagonism of pathogens such as Salmonella [ 103 ]. Furthermore, recent studies have observed that other dietary fibers, such as long-chain glucomannan, can reduce the colonization of Salmonella in the intestines of birds, thereby reducing the excretion of the bacteria into the environment, while also stimulating the immune response of the animal [ 104 ].…”
Section: Innovative Control Tools In Development Against S ...mentioning
confidence: 99%
“…Birds were fed either a control diet or diets with two different glucomannans at 0.02% or 0.20% inclusion levels. The inclusion levels of glucomannans were chosen based on the results from in ovo and in vivo broiler trials [13,14] and from previous studies with the same glucomannans on turkeys (non-published data). Glucomannans were labeled medium-chain glucomannan (MG) and long-chain glucomannan (LG) (Cargill Incorporated, Minneapolis, MN).…”
Section: Treatments and Experimental Designmentioning
confidence: 99%
“…Glucommanans is considered a feed additive with prebiotic effects that can be produced by combining cereal-derived mannose units to create different types of water soluble fibers. Previous studies with poultry have shown that glucomannans may have a positive impact on growth through modulation of the immune system, can act as prebiotics impacting gut microbiota, and by interacting with specific binding sites of the intestinal mucosa trigger physiological state [10,13,14].…”
Section: Introductionmentioning
confidence: 99%